Trade Policy and Redistribution When Preferences are Non-Homothetic - Do, Quy-Toan; Levchenko, Andrei A. (Elsevier, 2018)
We compare redistribution through trade restrictions vs. domestic lump-sum transfers. When preferences are non-homothetic, even domestic lump-sum transfers affect relative prices. Thus, contrary to the conventional wisdom, domestic lump-sum transfers are not necessarily superior to distortionary trade policy. We develop this argument in the context of food export bans imposed by many developing countries in the late 2000s.